Aplicación de la ecuación ipat para la proyección del impacto ambiental en el cantón buena fe, provincia los ríos, ecuador - Alcívar Castillo , David Xavier (2024)
This research on the application of the IPAT equation for the projection of environmental impact in the canton of Buena Fe, province of Los Ríos, Ecuador focused on using the IPAT equation to evaluate environmental impact. to do so, the population of the canton was simulated using asymptotic demographic models based on data from INEC. Statistical methods were used to estimate the average ecological footprint, collecting information through surveys from the Global Footprint Network. with these variables, the IPAT formula was applied to estimate the level of environmental impact in the short, medium and long term. The results revealed that the maximum sustainable population projection for the canton, according to the logistic model, was 198,999 inhabitants, while according to the Gompertz model it was 393,397 inhabitants. In addition, the variables of the IPAT equation were obtained: the representative sample consisted of 384 people, the inflow, represented by the ecological footprint of the canton, was 5.23 global hectares per person, and the technology, representing CO2 emissions, was equivalent to 1.66 tCO2eq/year. Finally, the environmental impact was calculated by applying the IPAT equation, with an impact generated in Buena Fe Canton of 3.3 ktCO2eq. This magnitude was projected for 5, 15 and 30 years using the logistic and Gompertz models.